The Influence of Hyperglycemia on Liver Triglyceride Deposition in Partially Pancreatectomized Rats - Bai, Xiu-Ping; Li, Ting-Ting; Guo, Lai-Li; Wang, Jing; Dong, Feng (Hormone and Metabolic Research, 2023)
Nonalcoholic fatty liver disease and diabetes always coexist. The relationship of fatty liver and hyperglycemia is not clear. We studied the influence of hyperglycemia on triglyceride (TG) accumulation in the liver and explored its possible mechanisms. SD rats were divided into three groups: Group A (sham operation control), Group B (partially pancreatectomized rats), and Group C (partially pancreatectomized rats treated with insulin). At 4 weeks after surgery, pancreatic weights and liver TG contents were measured. Serum biochemical parameters were determined, and oral glucose tolerance tests (OGTT) were performed. The gene expression of sterol regulatory element-binding protein1c (SREBP-1c), carbohydrate regulatory element-binding protein (ChREBP), fatty acid synthase(FAS), carnitine palmitoyltransferase 1 (CPT-1), and fibroblast growth factor 21 (FGF21) was determined by real-time PCR. Compared with Group A, postprandial glucose increased significantly; the concentrations of insulin and C-peptides, pancreatic weights and serum FGF21 levels were decreased, liver TG was increased significantly in Group B, and insulin treatment improved these changes. Compared with Group A, the gene expressions of FGF21, CPT-1 and FAS in the liver were decreased in Group B (all p<0.05). Compared with Group B, the gene expressions of FGF21, FAS, ChREBP, SREBP-1c and CPT-1 in the liver in Group C were all increased significantly (p<0.05, respectively). Hyperglycemia induced by partial pancreatectomy could lead to increased liver TG. Insulin treatment could decrease glucose levels and improve fatty liver, and genes related to lipid metabolism may play a role in this process.
Keywords: hyperglycemia; partial pancreatectomy; fatty liver; genes; lipid metabolism; metabolic syndrome